Efficient quantum dots anchored nanocomposite for highly active ORR/OER electrocatalyst of advanced metal-air batteries - Xu, Nengneng; Zhang, Yanxing; Zhang, Tao; Liu, Yuyu; Qiao, Jinli (Nano energy, 2019)
High activity bifunctional non-noble electrocatalysts, targeting both ORR and OER, are rationally designed by integrating the merits of both NiFe2O4 quantum dots and carbons nanotubes (CNTs) (NiFe2O4(QDs)/CNTs), which possesses large specific surface area (584 m2 g−1), abundant NiFe2O4 quantum dots and superior conductivity. Specially, the mechanism for the formation of quantum dots in relation to Fe/Ni ratio and the corresponding activity of ORR and OER are studied carefully. Consequently, NiFe2O4(QDs)/CNTs exhibits superior bifunctional oxygen electrocatalytic activities with the lowest the potential difference (ΔE) of 0.9 V, outperforming well-known commercial Pt/C and IrO2, directly demonstrating the advantages of quantum dots catalysts on providing more effective actives sites and adsorption-desorption sites to promote oxygen reaction kinetics. NiFe2O4(QDs)/CNTs, as high-performance catalyst used in liquid and flexible metal-air batteries, realize high power density, high specific capacity, long-term rechargeability (over 800 h), and extremely low charge-discharge voltage gaps (only 0.62 V) in ambient atmosphere. Furthermore, the metal-air batteries with flexible configuration effectively prevent the migration of Zn2+/Mg2+, the production of carbonate and the hydrogen evolution reaction. Density functional theory calculations further illustrate that the NiFe2O4(QDs) on CNT has a very active ORR and OER site at the interface Ni site. The work offers prospects for the rational design of quantum dots containing composites to achieve their practicalities in next generation of metal-air batteries. Quantum dots bifunctional catalyst is synthesized on the basis of a governable nanoscale designed strategy. The mechanism of the formation of quantum dots is revealed. Importantly, NiFe2O4(QDs)/CNTs, due to the effect of quantum dots and the strong coupling, can rapidly accelerates the oxygen electrochemical process and demonstrates enormous potential in liquid and flexible metal-air battery. [Display omitted] •A tunable nanoscale designed strategy was proposed to synthesize newly bifunctional quantum dot catalyst.•NiFe2O4(QDs)/CNTs demonstrates excellent activity and stability for ORR and OER.•NiFe2O4(QDs)/CNTs is used as a cathode material for metal-air battery and its flexible devices for the first time.•Liquid/ flexible magnesium-air batteries assembled with NiFe2O4(QDs)/CNTs exhibits the best performance ever reported.•DFT calculations illustrate that the NiFe2O4(QDs) on CNT have an active ORR and OER site at the interface Ni site.